2022
DOI: 10.5607/en22024
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Septum Somatostatin Neurons are Activated by Diverse Stressors

Abstract: The lateral septum (LS) is a forebrain structure that has been implicated in a wide range of behavioral and physiological responses to stress. However, the specific populations of neurons in the LS that mediate stress responses remain incompletely understood. Here, we show that neurons in the dorsal lateral septum (LSd) that express the somatostatin gene (hereafter, LSd Sst neurons) are activated by diverse stressors. Retrograde tracing from LSd Sst neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Previous studies have reported that NE enhances excitatory synaptic transmission to LS SST neurons, but does not affect stress-related behaviors. [50] This was consistent with our finding that NE was not required for the LC TH -dLS circuit to alleviate social avoidance following social trauma. We acknowledge that BDNF has been extensively studied in depression, yet there is no consensus in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that NE enhances excitatory synaptic transmission to LS SST neurons, but does not affect stress-related behaviors. [50] This was consistent with our finding that NE was not required for the LC TH -dLS circuit to alleviate social avoidance following social trauma. We acknowledge that BDNF has been extensively studied in depression, yet there is no consensus in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, Sstexpressing cells (>50% in dorsal LS; >40% in intermediate LS) and Calb1-expressing cells (almost 40% in dorsal LS; almost 30% in intermediate LS) represent most Avpr1a-expressing cells in the LS, suggesting important roles for both subtypes of GABAergic interneurons in V1aR-mediated functions in the LS. Enhanced activity of Sst-expressing neurons in the dorsal LS is associated with increased anxiety-like behaviors (Besnard et al, 2019;An et al, 2022) while suppressed activity of Sst-expressing neurons in the dorsal LS is associated with improved social discrimination behavior (Borie et al, 2021) in mice. Calb1 is almost exclusively expressed in GABAergic neurons in the LS (Zhao et al, 2013), but the function of Calb1-expressing cells in the LS seems unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the discrepancy in signal between water, alcohol, and sucrose indicates precise tuning relative to the rewarding properties of these liquids. Because discrete cell types within the LS are tuned to aversive stimuli [44][45][46] , we then assessed LS Pnoc activity in response to footshock and air puff exposure. Footshock elicited a robust increase in LS Pnoc Ca activity in males and females (Fig.…”
Section: Ls Pnoc Respond To Stimuli Associated With Negative Valencementioning
confidence: 99%
“…Indeed, the LS has been implicated in stress and anxiety states, and recent studies leveraging in vivo Ca imaging techniques have revealed heightened activity in genetically defined LS populations during exposure to stimuli associated with negative valence. For example, NTS- 46,57 , SST- 45 , and CRFR2- 44 expressing neurons in the LS are responsive to footshock, and VGAT-expressing neurons are highly responsive to pain 58 . LS Pnoc activity follows this pattern, displaying increased activity during footshock, air puff stimulus, sucrose spray, as well as exploration of the open arm in an EPM.…”
Section: Aud Neurocircuitry: Role For the Lateral Septum In Binge Dri...mentioning
confidence: 99%